2016
DOI: 10.1111/jgs.14502
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Chewing Difficulty and Symptoms of Depression in Adults: Results from the Korea National Health and Nutrition Examination Survey

Abstract: Chewing difficulty was independently associated with symptoms of depression in a representative sample of Korean adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It was reported that cognitive function significantly decreased as the number of remaining teeth decreased [4, 13, 14, 16]. If teeth are lost, chewing efficiency and function are reduced, which decreases the ability to perform everyday activities and the quality of life and increases the risk of conditions like depression [2022]. Also, the reduction of chewing functions might decrease learning and memory abilities [23–25].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that cognitive function significantly decreased as the number of remaining teeth decreased [4, 13, 14, 16]. If teeth are lost, chewing efficiency and function are reduced, which decreases the ability to perform everyday activities and the quality of life and increases the risk of conditions like depression [2022]. Also, the reduction of chewing functions might decrease learning and memory abilities [23–25].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, bolus size barely changes, thus bolus particles are larger in those not maintaining natural dentition [ 22 , 23 ]. Perceived inability to mash food has been associated with mild dysgeusia [ 24 ], digestive and psychological stress [ 25 ], as well as with depression [ 26 ]. Second, taste perception is also affected by taste bud receptors’ density and functionality.…”
Section: Can We Maintain Sensitivity Against Food Modalities Over mentioning
confidence: 99%
“…In clinical practice, at least the pharmacological management of depression is problematic, because of the established risk of MCI due to anticholinergic medication [ 187 ]. Simple modifications though in daily routine may have considerable impact on neuropsychiatric symptoms independently of disease stage [ 2 ], addressing even disregarded physiological causes, such as chewing difficulties [ 26 ]. Positive reinforcement could also be advantageous, as reduced attention during meals has been shown to associate with poor appetite, and Geriatric Depression Scale ratings, in both MCI and AD, and despite concurrent psychoactive medication in AD [ 184 ].…”
Section: The Emerging Role Of Salience Network In Appetite Regulamentioning
confidence: 99%
“…Chewing ability refers to individuals' masticatory performance in chewing selected common foods. 16 Previous studies suggested older adults who have poor chewing ability are more prone to experience insufficient nutrient intake, 17 impaired cognition, 18 and depression. 19 In addition, few community-based surveys reported chewing ability was associated with frailty.…”
Section: Introductionmentioning
confidence: 99%